Research on active composition and biological activity in different polar extracts of Nostoc commune - CHEN Fuzhang, YUAN Zhenzhen, JIN Suyu, LI Yaqian, SONG Xiaofan, SUN Kangna, HAN Lijuan, YE Ying (Zhongguo niangzao)
In order to study the active components contents in different polar extracts of Nostoc commune and their antioxidant and antibacterial effects in vitro, 4 polar extracts including petroleum ether phase, ethyl acetate phase, n-butanol phase and water phase were obtained by ultrasonic-assisted extraction method. The contents of total triterpenes, total flavonoids, and total polyphenols in 4 different polar extracts were determined. Using vitamin C (VC) as the control, the radical scavenging of different polar extracts on ABTS+, DPPH, O2- free radical, and reducing power were determined. The inhibition zone size and its antibacterial activity were measured by filter paper method. The results showed that the contents of total triterpenes, total flavonoids and total polyphenols in ethyl acetate phase of N. commune were 0.33%, 2.40% and 0.67%, respectively. All polar extracts had certain antioxidant activity and antibacterial activity. Among them, the extract of ethyl acetate phase had the optimal antioxidant capacity and antibacterial activity. The study provided a theoretical basis for the utilization of bioactive substances in N. commune and the development of antioxidant products of N. commune.